The Growth of Coastal Cottonwood (Hibiscus tiliaceus Linn.) Seedlings by Inoculating Arbuscular Mychorrhiza Fungi (AMF) on Sand Beach Planting Media - Nailul Rahmi Aulya; Zozy Aneloi Noli; Suwirmen Suwirmen (Universitas Andalas, 2020)
Hibiscus tiliaceus L. is a seaside plant that has several benefits, one of which is as a producer of paper fiber. H. tiliaceus need a better nutrient to grow on coastal land that is still constrained by the high level of salinity. By this, a special treatment is needed to support its growth. One of them is the application of mycorrhizal inoculants. Mycorrhizae is known as one of the fungi that can help plants tolerate salinity. The aims of the research were to determine the effect of AMF inoculants and determine the best doses of AMF to the seedling growth. The research used completely randomized design with 5 treatments and 5 replications. The treatments were (A) without AMF (control), (B) inoculation AMF 10 g/plant, (C) inoculation AMF 15 g/plant, (D) inoculation AMF 20 g/plant and (E) inoculation AMF 25 g/plant. The result showed that AMF can infect the roots of hibiscus seedlings with an infection degree of 18-34%. However, it has not been able to have a significant effect on shoot length, number of leaves, dry weight of root, and dry weight of shoot.